Overbidding in Fixed Rate Tenders - An Empirical Assessment of Alternative Explanations - Dieter Nautz; Jörg Oechssler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
This paper investigates various theories explaining banks' overbidding in the fixed rate tenders of the European Central Bank (ECB). Using auction data from both the Bundesbank and the ECB, we show that none of the theories can on its own explain the observed overbidding. This implies that the proposed new rules by the ECB, aimed at neutralizing interest rate expectations, would not eliminate overbidding if the rationing rule in the fixed rate tenders remains unchanged.
Keywords: E52; D44; 330; Overbidding; repo auctions; monetary policy instruments of the European Central Bank; Pensionsgeschäft; Zins; Bank; Auktionstheorie; Europäische Wirtschafts- und Währungsunion; EU-Staaten; Zinstender